A Facile One‐Pot Method for Fabricating Assembled Gold Nanoparticle Films with Tunable Morphologies Directly from Chloroauric Acid. Issue 18 (31st August 2021) - Wu, Qiu‐yan; Wu, Peng; Zhong, Lu‐bin; Zhang, Qi‐jun; Zhao, Xue‐qin; Zheng, Yu‐ming
Abstract: Assemblies of nanoparticles possess extensive potentials for various applications due to their unique properties. These properties are significantly related to the morphology (size, shape) and spatial positioning of nanoparticles. To meet the needs of different application fields, it is important to tune the structures of assemblies in a controllable way. Currently, the morphology control and assembly of nanoparticles are generally conducted in two separate steps, which cannot resolve the contradiction between the need of sufficient surface charge for stabilizing nanoparticles and the necessity of overcoming the electrostatic repulsion during self‐assembly process. In this study, a simple one‐pot method to fabricate assembled gold nanoparticles (AuNPs) films with tunable morphologies is proposed. AuNPs are synthesized and self‐assembled simultaneously at cyclohexanone–water interface. The cyclohexanone in this system not only reduces the chloroauric acid solution to form AuNPs, but also establishes an oil–water interface with low interface energy, which can capture the AuNPs effectively for forming an ordered array. Furthermore, the morphologies of AuNPs are manipulated by simply tuning pH of the chloroauric acid solution. The fabricated AuNPs films with different morphologies are demonstrated to be applicable for surface enhanced Raman scattering detection, catalytic monitoring, and sensing. Abstract : Assembled gold nanoparticle films with various morphologies are fabricated directly from chloroauric acid without any surfactant by designing a low interfacial energy water‐cyclohexanone biphasic system. The fabricated films have different morphologies and properties, which can be applied in different areas, such as in flexible conductors, surface‐enhanced Raman scattering detection, and catalysis monitoring.